ENVIRONMENTAL INNOVATIVE BUSINESS SOLUTIONS AS A STRATEGIC FACTOR OF ECONOMIC SECURITY ISSUES - A. S. Senin; O. Nikandrova (Модернизация, инновация, развитие, 2016)
The relevance of this work lies in the fact that it attempts to disclose the key theoretical and practical issues of economic security solutions, taking into account the problems of global transformations taking place in the global economy. As part of the article we have been studied various aspects that characterize global economic, environmental trends that will shape the future of modern civilization. The article also addresses the problem of exit from the raw model of the economy, the formation of economic mechanisms that take into account environmental costs, proposed internalization of environmental externalities.The purpose/goal. The purpose of this article and its main task is to systematize the areas of environmentally oriented development of economic entities, as well as the determination of the list of key provisions of environmental policies, which will ensure the further socio-economic development of Russia in line with the green economy.Methods. In this article, based on content analysis of theoretical and empirical basic conceptual provisions of economic security were formulated in the context of eco-oriented production, the transition to which world civilization is currently implementing. It was concluded that the economic, energy, environmental and social issues of sustainable development of modern civilization is directly linked, so the transition to ecooriented production is possible, firstly, it provided aggressive reduction of production and wasteful use of traditional hydrocarbon resources, and, secondly, on the condition of rational replacement of traditional energy sources with renewable energy.Results. This article outlines the basic solutions that can be used to provide environmentally responsible operation and development of Russian business and corporate structures. Also offered in the basic decisions that are to be included in the national environmental policy as a major incentive for the further transition to a sustainable and green economy.Conclusions / relevance. The above article further aspects of environmentally responsible operation and development of Russian business and corporate structures can complement scientific and practical base solutions that provide active creation, implementation and use of green technologies to provide environmentally responsible sustainable socio-economic development.